Perfil proteômico do corpo gorduroso de larvas de Diatraea saccharalis (Lepidoptera: Crambidae) sob condição de injúria séptica causada por microorganismos - Seuchuco, Charles (2018)
Diatraea saccharalis, known as a sugarcane borer, is a moth of the Lepidoptera order, being one of the main pests on sugarcane, responsible for damage to the sugar and alcohol industries. The fat body is the organ responsible for several functions during the larval phase of insects, mainly in charge of synthesizing molecules with metabolic actions. The success in insects’ adaptation is due to its efficient defense system, in which the fat body is able to synthesize antimicrobial peptides (AMP’s) and secrete them in the hemolymph, where they act as a defense mechanism against pathogens. AMP’s has a cationic character and present the capacity to interact with negative charge molecules of the bacteria, leading to the disintegration of their membranes. Considering the concerns regarding bacterial resistance to antibiotics and antimicrobial properties of AMP’s, such as fast-acting, varied mechanisms of action and wide range against Gram-positive and Gram-negative bacteria; it has become appropriate to carry out studies to use AMP’s as alternative or complementary antibiotic. In D. saccharalis, AMP’s with antimicrobial action have been reported in recently published papers using proteomic methodology. Thereby, this study aimed to perform the differential analysis of the proteins and peptides of the fat body in the 5th instar of larvae challenged with Escherichia coli, Bacillus subtilis and Beauveria bassiana; using the two-dimensional electrophoresis technique (2-DE), with 12.5% SDS-PAGE tricine gels, MALDI-TOF type mass spectrometry and the research in protein databases (Mascot and TagIdent). After analysis, six defense proteins of the innate immune system were found using the TagIdent identification tool: apolipophorin-3, attacin, attacin-F, Peptidoglycan recognition protein (PGRPs), putative defense protein 1 and putative defense protein 3. The AMP attacin presented a positive regulation in relation to the control gel indicating that the B. bassiana septic challenge stimulated the immune system of D. saccharalis. This study provides the first reports of proteins of the immune system produced by the adipose tissue of D. saccharalis.